Improving Learning Outcomes of Catholic Religious Education for Grade III Students Through The Storytelling Method - Maria Yulita C. Age; Bernadeta Dhey (CV. Syntax Corporation Indonesia, 2024)
Learning outcomes are the mastery and abilities that students have achieved about the material and skills regarding the subject after receiving their learning experience. Learning outcomes can be measured from their own abilities, where in the learning process in the classroom students are more active and the ability of Catholic Religious Educator teachers to apply skills to the teaching and learning process can improve student learning outcomes. In teaching and learning activities at SDK Puubheto, especially in grade III Catholic Religious Education lessons, problems were found in teaching and learning activities, namely; Students feel bored because the classroom atmosphere is not conducive, teachers do not understand the right learning methods according to the age of students and are not skilled in applying learning methods, students are not actively involved in teaching and learning activities, teachers tend to only give assignments so that students lack understanding of the material, and student learning outcomes are low. The formulation of the problem in this study is how the influence of the storytelling method on improving student learning outcomes. The purpose of this study was to determine how the influence of the application of storytelling learning methods on Catholic Religious Education subjects in improving learning outcomes. In improving learning outcomes, researchers use the application of storytelling methods in Catholic Religion subjects. The storytelling method is a learning strategy where the delivery is through oral speech by telling stories or events and information that is packaged creatively to attract children's attention. The results of the study found by researchers showed that the learning outcomes of students in each cycle increased from the pre-test results with a percentage of 35.71%, the percentage of post-test cycle I of 50%, and the percentage of post-test cycle II of 100%. It can be said that there is an increase in the learning outcomes of Catholic Religious Education through the application of storytelling methods in grade III of Puubheto Catholic Elementary School.